STUDY ON PROFILE MODIFICATION OF GEAR COUPLING USED IN PLANETARY TRANSMISSION - TAN YuanQiang; HUANG Bin; WANG Wen; HU CongFang; ZHANG Yong (Jixie qiangdu)
For the planet transmission device whose sun gear shaft is connected with tooth coupling,floating displacement of the sun gear directly determines tilt angle compensating of the tooth coupling,However,because of the sun gear ’s floating displacement multiply affects by comprehensive errors of planetary gear train parts,Its real value is difficult to calculate and measure accurately. This paper proposed a method,which is based on the dynamics analysis principle,to solve the sun gear’s floating displacement. It applies the means of equivalent meshing error to consider the manufacture and installation error of planetary gear train key components,a dynamic model of planetary gear train has been built,and according to the geometric relations between drum shaped spline and sun gear shaft,the tooth profile of drum gear has been modified to reduce the misalignment of the two connecting shafts. Finally,the experiment of certain planetary-gear transmission demonstrates that theoretical model is correct and possesses significant value of engineering applications.